(untitled) (Jurnal Destinasi Pariwisata, 2026)
Waerebo Tourism Village is one of the leading tourist destinations in East Nusa Tenggara (NTT) Province, renowned for its natural beauty and the unique architecture of its traditional Mbaru Niang houses. In addition to these attractions, the village has also begun to develop coffee agrotourism as a complementary tourism product. The development of coffee agrotourism is carried out by utilizing the available resources within the local environment. This study aims to examine the current condition of community-based coffee agrotourism in Waerebo Tourism Village, to identify internal and external factors influencing its develop ment, and to formulate strategies that can be implemented to support its growth. To achieve these objectives, the study employs a qualitative descriptive research method through field observations, interviews, literature review, and documentation. Informants were selected using purposive sampling, while data were analyzed using qualitative descriptive techniques and SWOT analysis. The findings indicate that the coffee agrotourism products developed by the local community meet the 5S criteria in tourism product development standards. However, coffee agrotourism has not yet become the main focus of tourism attraction development in Waerebo Village. Furthermore, the identification of internal and external factors revealed several elements that influence the development of coffee agrotourism in Waerebo, including: the village’s status as a well-known tourist destination; community awareness of the importance of preserving Waerebo’s culture and natural environment; fertile agricultural land; farming as the main livelihood of the local population; the community’s openness to visitors; limited accommodation facilities; coffee agrotourism packages that require a relatively long length of stay; underdeveloped promotional efforts; most plantations being located far from the village and having limited access; advancements in information technology; collaborative partnerships with various stakeholders; the existence of two residential areas for the local population; the influence of technological development in agriculture; and the potential for internal conflict among local residents. The strategies formulated through the SWOT matrix analysis include: development of flexible coffee agrotourism attractions, provision of alternative accommodations, enhancement of promotional activities, implementation of an online reservation and payment system, development of creative and educational tour packages, establishment of functional working groups, and strategies for community outreach and education.